Mapping Iranian Patents from 1976 to 2011 Based on International Patent Classification(IPC) - Saman Ravand; Alireza Noruzi; Mohammad Hiwa Abdekhoda (Tehran University of Medical Sciences, 2012)
Background and Aim: Patents are used as indicators to assess the growth of science and technology in a given country or area. They are examined to determine the research potentials of research centers, universities, and inventors. This study aims to map the past and current trends in patenting activities with a view to understanding better and tracking the changing nature of science and technology in Iran. Materials and Methods: The patenting activity in Iran was investigated based on USPTO, WIPO, and Esp@cenet for the period 1976-2011. The researchers analyzed the affiliation of inventors, and collected patents having at least one Iranian inventor. The collected data were analyzed using Microsoft Excel. Results: results showed that between 1976 and 2011, 212 patents were registered by Iranian inventors in the above-mentioned three databases. The average number of Iranian patents registered per year increased significantly from 25 in 1976-1980 to 119 in 2006-2011. It should be noted that the highest number of registered patents (27%) were in" chemistry, metallurgy" area of International Patent Classification, followed by "human necessities"(18%), and "performing operations; transporting"(15%). Conclusion: Overall, the proportion of Iranian inventors' patents registered in databases is small. However, the figure shows a growth for the years under study. Iran's patents registered in databases have considerable subject concentration. Scientific areas are growing together, and there is more potential of research work and innovation in areas of "chemistry, metallurgy", "Electricity" and "human needs".